South Africa's Exports Performance : Any Role for Structural Factors? - Anand, Rahul; Perrelli, Roberto; Zhang, Boyang (Washington, D.C. : International Monetary Fund, 2016)
Despite a substantial and prolonged exchange rate depreciation, South Africa's export performance has disappointed since the global financial crisis. In this paper we focus on the role of structural factors in reducing the responsiveness of South African exports to the real exchange rate depreciation. To this end, we construct a unique database of export performance at the firm level. Our analysis suggests that electricity bottlenecks, limited product market competition, and labor market constraints have reduced the responsiveness of firms' exports to the rand depreciation. On the other hand, a firm's ability to diversify its exports has helped it benefit more from currency movements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet